Assessing the predictive validity of perceived globalness and country of origin of foreign brands in quality judgments among consumers in emerging markets. Issue 5 (29th May 2020) - Han, C. Min
Abstract: Consumers in emerging markets are known to have strong preferences for well‐known foreign brands. Drawing on schema and categorization theories, this study empirically investigates how accessible two components of brand foreignness – globalness and country of brand origin – are in consumer perceptions of brand quality in emerging markets. In addition, we argue that brand globalness can be shaped by inferential reasoning and test how consumer perceptions of brand globalness are affected by both a brand's country of origin and its perceived quality. Two different studies were conducted with young‐adult consumers in China. The study found that in their evaluations of foreign brands consumers are more influenced by country of origin than by brand globalness. It also found that consumers tend to perceive a high level of globalness in high‐quality brands and brands from a favorable country‐of‐origin. Further, this tendency was found to differ between well‐known and lesser‐known brands. These findings confirm the predictive validity of country of origin, but contrast with extant literature on the role of brand globalness as a principal quality cue for foreign brands among consumers in emerging markets. Our findings also imply brand globalness can be an inferred attribute of perceived brand quality and country‐of‐origin image. Keywords: brand foreignness, brand globalness, country‐of‐origin effect, emerging markets.